Relative Copy Number Variations of CYP2C19 in South Indian Population. (25th June 2012) - Devendran, Anichavezhi; Uppugunduri, Chakradhara Rao Satyanarayana; Sundaram, Rajan; Shewade, Deepak Gopal; Rajagopal, Krishnamoorthy; Chandrasekaran, Adithan
Abstract : CYP2C19 is a polymorphic enzyme involved in the metabolism of clinically important drugs. Genotype-phenotype association studies of CYP2C19 have reported wide ranges in the metabolic ratios of its substrates. These discrepancies could be attributed to the variations in the promoter region and this aspect has been reported recently. The observations in the recent reports on the influence of promoter region variants on the metabolism of CYP2C19 substrates might also have been influenced by the copy number variations of CYP2C19 . In this paper, we describe copy number variations of CYP2C19 using real-time polymerase chain reaction by comparative Ct method. No copy number variations were observed in the south Indian population indicating the observed discrepancies in genotype-phenotype association studies might be due to the regulatory region polymorphisms as reported earlier.